2016
DOI: 10.1159/000447721
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Abdominal Adhesions Make the Interpretation of Magnetic Resonance Enterography in Crohn's Disease More Difficult

Abstract: Aims: The present study compares preoperative magnetic resonance enterography (MRE) accuracy in diagnosing stenoses, abscesses and fistulas to intraoperative findings in Crohn's disease patients, and determines whether discordance between these methods alter surgical plans. Methods: Our study included 55 consecutive patients scheduled for elective surgery due to Crohn's disease in a single institution between January 2011 and May 2015, whose surgical findings were also compared to preoperative MREs. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies with SICUS or CEUS were included (three studies) and analyzed to determine whether they were better than the conventional US. Previous studies reported superior sensitivity in the detection of small bowel lesions with SICUS (96–100% vs. 57–96%) and reduced interobserver variability compared with the conventional US [ 38 ]. Likewise, the previous meta-analysis reported the pooled sensitivity, specificity, and summary AUC of CEUS for an active CD to be 93%, 87%, and 0.96, respectively, which were superior to those of US in our study [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with SICUS or CEUS were included (three studies) and analyzed to determine whether they were better than the conventional US. Previous studies reported superior sensitivity in the detection of small bowel lesions with SICUS (96–100% vs. 57–96%) and reduced interobserver variability compared with the conventional US [ 38 ]. Likewise, the previous meta-analysis reported the pooled sensitivity, specificity, and summary AUC of CEUS for an active CD to be 93%, 87%, and 0.96, respectively, which were superior to those of US in our study [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the diagnosis of CD can be simple in the upper gastrointestinal tract or in the colon as they can be easily assessed in endoscopy, the large area of the small bowel is difficult to access in conventional endoscopy. Magnetic resonance enterography (MRE) can be used to detect severe lesions like transmural inflammation, stenosis, fistulae or extraintestinal abscesses [ 2 , 3 ]. MRE is not sensitive enough to detect luminal lesions in the small bowel [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%